UNVEILING THE CENTRAL MECHANISM: ICFR AS A MEDIATOR OF HUMAN CAPITAL AND TECHNOLOGY IN PUBLIC SECTOR FINANCIAL REPORTING QUALITY - Risti’ani Malik Janisoleha; Sugeng Haryanto; Nanik Sisharini (Adisam Publisher, 2026)
This study investigates the determinants of Financial Reporting Quality (FRQ) within the unique institutional context of Indonesian District Courts, focusing on the mediating role of Internal Control over Financial Reporting (ICFR). While prior public sector accounting literature offers inconsistent findings regarding the direct effects of Human Capital (proxied by Financial Management Policy, X1) and Financial Applications (X2) on FRQ, this research proposes that ICFR (Y1) functions as the critical mechanism translating these resources into reliable reporting outcomes (Y2). Employing a quantitative explanatory design, data were collected from 175 financial management officers across District Courts in East Java, institutions characterized by centralized governance and standardized financial systems (e.g., SAKTI, E-Rekon). Path analysis results reveal that Financial Applications exert a stronger influence on ICFR than Financial Management Policy. Crucially, ICFR emerged as the most significant predictor of FRQ. The mediation analysis confirms that ICFR partially mediates the X1-Y2 relationship and dominantly mediates the X2-Y2 relationship. This finding underscores the shift toward system-dependent controls in centralized public institutions, where technological infrastructure effectively institutionalizes internal controls. The study extends public sector accounting theory by integrating Agency Theory, Human Capital Theory, and the Technology Acceptance Model within a unified mediation framework, offering practical insights for strengthening governance and internal control systems within the judiciary to achieve high-quality financial reporting and unqualified audit opinions